Medical Texts and Their Translation in Translator Training - Gabriella Kovács (Acta Universitatis Sapientiae: Philologica, 2023)
With the development of medicine, the demand for the translation of medical texts has increased significantly. Translations play an important role in disseminating medical knowledge and new medical discoveries and are vital in the provision of health services to foreigners, tourists, or minorities. Translating medical texts requires a variety of skills. In our study, we assess the extent to which translation and interpretation students at Sapientia Hungarian University of Transylvania are able to translate medical texts from English into their mother tongue (Hungarian) and Romanian (the official language of the country). With the purpose of curriculum development, we examine whether the lack of medical knowledge affects the work of translators and what strategies can be used in translation in the absence of this expertise. We also examine our students’ attitude related to translating medical texts and becoming a medical translator.